Everyday cake : 45 simple recipes for layer, bundt, loaf, and sheet cakes - Chesnakova, Polina (Sasquatch Books, 2022)
"In Everyday Cake, the recipes are easy, relatively quick to prepare and bake in one pan, and use ingredients that are readily available"--